2004
DOI: 10.1002/cncr.20392
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic screening: Patterns of use and estimated impact on breast carcinoma survival

Abstract: BACKGROUNDAlthough many studies support the life‐saving potential of screening mammography, the actual utilization of screening and the impact of the actual pattern of screening use on the breast carcinoma death rate, remain incompletely understood. In the current report, the authors describe patterns of screening use among women who were examined at a large screening and diagnostic service and estimate the added mortality associated with missed screening mammograms.METHODSMammography use was assessed in a pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 26 publications
5
72
2
3
Order By: Relevance
“…The relationship was not seen for mammography. Studies in other populations have found that those who speak a language different than English at home tend to have lower breast and cervical cancer screening prevalences, although similar findings have not been reported for American Indian and Alaska Native populations [7,26,27]. Examining predictive factors specific to Alaska and to the Southwest revealed that the finding was most apparent in Alaska.…”
Section: Discussionmentioning
confidence: 77%
“…The relationship was not seen for mammography. Studies in other populations have found that those who speak a language different than English at home tend to have lower breast and cervical cancer screening prevalences, although similar findings have not been reported for American Indian and Alaska Native populations [7,26,27]. Examining predictive factors specific to Alaska and to the Southwest revealed that the finding was most apparent in Alaska.…”
Section: Discussionmentioning
confidence: 77%
“…However Mammography findings were normal in all these individuals. [15][16][17] This study showed that more than 50% of the women were informed about BSE and its importance and its trends with respect to age, heredity and early detection.…”
Section: Resultsmentioning
confidence: 95%
“…A review of data on repeat mammography found that in studies whose participants had an on-schedule recent mammogram, at least 70% went on to obtain subsequent on-schedule exams (2). A report by Blanchard et al (14) also found that having a prior on-schedule mammogram was associated with a higher rate of repeat screening than for women without one on record. On the one hand, past behavior is generally a strong predictor of future behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, estimates ranged from as low as 28% (3,4) to as high as 92% (5). Studies since that review continue to report varying rates of repeat mammography, even when there were different subgroups examined in a single report: 45% and 49% (6); 67% and 74% (7); 73.4% (8); 29.9% and 35.8% (9); a range of 33% to 67.5% across six samples (10); 72.4% and 81.5% (11); 41% (12); 41.4% (13); 16%, 42%, and 63% (14); 79.8% (15); and 44% and 65% (16). The differences among these rates both within and between studies are due to their different samples and sampling frames, which are often local; the definitions of repeat mammography, including different intervals allowed between exams; and sometimes long elapsed times between when data were collected and when publication occurred, which does not account for secular trends during the elapsed time before publication.…”
Section: Introductionmentioning
confidence: 99%